Survey on Tweet Segmentation and Sentiment Analysis - Ansari, SS; Diwan, T (International Journal of Computer Sciences and Engineering, 2025)
With the explosive growth of user generated messages, twitter has become a social site where millions of users can exchange their opinions. Sentiment analysis on twitter data plays an important role in finding public opinions which have provided an economical and effective way timely, which is very useful for decision making in various domains. A company can take the public opinion in tweets to obtain user review towards its products where a politician can adjust his position with respect to the opinion change of the public. There have been a large number of research studies and industrial applications in the area of public sentiment tracking and modeling. Millions of users give their opinions on Twitter, making it a valuable platform for tracking and analyzing public sentiment. Such tracking and analysis can provide critical information for decision making in various domains. So, it has attracted attention in both academic and industry. Previous researches showed that the tweet was classified appropriately only if the tweet would contain the exact same label as the training set. But this approach fails when the tweet contains a synonym or a variant of the label instead of the exact same label.